1997
DOI: 10.1097/00006842-199701000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Social Dominance and 22-Year All-Cause Mortality in Men

Abstract: These results suggest that, in future research concerning psychosocial factors and long-term survival, attention should be given to social dominance as well as to hostility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Consistent with these findings, the cardiovascular correlates of trait dominance mentioned above seem to suggest a more adaptive stress-related response for high compared to low dominant subjects (Dienstbier, 1989;Tomaka et al, 1993). This interpretation, however, contradicts empirical findings that found dominant behavior to be related to coronary heart disease (CHD) and allcause mortality (Houston et al, 1992;Houston et al, 1997). Research on nonhuman primates and human subjects indicates that the psychosomatic risk of dominant behavior may partly be determined by environmental characteristics.…”
Section: Introductionmentioning
confidence: 84%
“…Consistent with these findings, the cardiovascular correlates of trait dominance mentioned above seem to suggest a more adaptive stress-related response for high compared to low dominant subjects (Dienstbier, 1989;Tomaka et al, 1993). This interpretation, however, contradicts empirical findings that found dominant behavior to be related to coronary heart disease (CHD) and allcause mortality (Houston et al, 1992;Houston et al, 1997). Research on nonhuman primates and human subjects indicates that the psychosomatic risk of dominant behavior may partly be determined by environmental characteristics.…”
Section: Introductionmentioning
confidence: 84%
“…Other personality types have included "type D" personality, 17 "social dominance," 58 and a "hardy personality" construct 59 ; these latter personality types have not been widely studied as potential risk factors for CAD. Interest in type A behavior accelerated after the Western Collaborative Group Study, which reported that type A behavior was associated with a 2-fold increased risk of CAD and 5-fold increased risk of recurrent MI over an 8.5-year follow-up.…”
Section: Personality and Character Traitsmentioning
confidence: 99%
“…Algunos estudios, sin embargo, han puesto de relieve la existencia de datos respuesta y tasa rápida del habla, Houston et al, 1997), se han asociado a incrementos de la presión sanguínea (Brown y Smith, 1992) o a incrementos por cualquier causa de la mortalidad (Houston et al, 1997). En esta línea de evidencia, Guyll y Contrada (1998) observaron elevaciones de la presión sanguínea entre las personas más hostiles sólo durante los periodos de interacción social.…”
Section: La Hostilidad: ¿Un Factor Gene-ral De Riesgo Cardiovascular?unclassified